Learning to Read Talmud What It Looks Like and How It Happens - Kanarek, Jane L.; Lehman, Marjorie (Academic Studies Press, 2019)
Finalist, 2017 National Jewish Book Award for Education and Jewish Identity"Learning to Read Talmud" is the first book-length study of how teachers teach and how students learn to read Talmud. Through a series of studies conducted by scholars of Talmud in classrooms that range from seminaries to secular universities and with students from novice to advanced, this book elucidates a broad range of ideas about what it means to learn to read Talmud and tools for how to achieve that goal. Bridging the study of Talmud and the study of pedagogy, this book is an essential resource for scholars, curriculum writers, and classroom teachers of Talmud.